GEOGRAFI KEJAHATAN, TEORI DISORGANISASI SOSIAL, DAN KAJIAN TERHADAP KEJAHATAN DI RUANG PERKOTAAN - Olii, Mohammad Irvan (UI Scholars Hub, 2019)
Spatial distribution of crime at urban space has long been part of geographical studies. One theory that been used to examine such spatial distribution is Social Disorganisation Theory. This article will review the used of social disorganization theory on an article by de Melo, Andersen and Matias (2017) which studied geography of crime in a Brazilian city. This article will also briefly explain the historical context of the aforemention theory with its connection to studies of urban problems, especially crime problems, and also the basis thought of the theory that exist. The critiques of social disorganisation theory will also be explain. At the end of the article, it will explain differences of comprehending urban space based on the social disorganization theory and the urban space on Indonesian contex